Clinical Evaluation of High-Volume Hemofiltration with Hemoperfusion Followed by Intermittent Hemodialysis in the Treatment of Acute Wasp Stings Complicated by Multiple Organ Dysfunction Syndrome. - Xiaoyun Si; Jingjing Li; Xiaohong Bi; Lan Wu; Xiaoyan Wu (PLoS ONE, 2015)
Multiple organ dysfunction syndrome (MODS) is a rare complication of wasp stings. Currently, there is no standardized treatment for MODS secondary to multiple wasp stings, although blood purification techniques are often used. This study aimed to analyze our experiences of using intermittent hemodialysis (IHD) with or without high-volume hemofiltration (HVHF) for treating acute wasp stings complicated by MODS. In this retrospective study, 36 patients with wasp stings complicated by MODS received either IHD combined with hemoperfusion, or HVHF (ultrafiltration flow rate, 70 mL/kg/h) combined with hemoperfusion for 5 days followed by IHD. Clinical symptoms, blood biochemical parameters, duration of mechanical ventilation, use of vasoactive agents, duration of hospital stay and survival rate were recorded, and Acute Physiology and Chronic Health Evaluation II (APACHE II) and multiple organ dysfunction (MOD) scores estimated. Patients treated with HVHF followed by IHD appeared to exhibit a faster recovery than those receiving IHD alone, as evidenced by superior improvements in MOD (4.29±1.08 vs. 2.27±1.07) and APACHE II (7.09±2.62 vs. 4.20±1.69) scores (P < 0.05). Patients treated with HVHF had significantly lower myoglobin, creatine kinase-MB, lactate dehydrogenase, bilirubin and creatinine levels than patients treated with IHD alone. In addition, the durations of hospital stay (13.15±2.77 vs. 27.92±3.18 days), vasopressor use (1.76±0.24 vs. 3.43 ± 1.01 days), mechanical ventilation (3.02±1.63 vs. 5.94 ± 2.11 days) and oliguria (6.57±2.45 vs. 15.29 ± 3.51 days) were reduced, and renal function more often recovered (85.1% vs. 53.1%), in the HVHF group compared with the IHD group (P < 0.05). These results raise the possibility that HVHF plus IHD may be superior to IHD alone for the treatment of acute wasp stings complicated by MODS; additional prospective studies are merited to explore this further.